(untitled) (Al-Qamar, 2022)
Saeed Naqvi is a well-known poet, scholar and a rising star of Urdu literature. He proved his intelligence through his written works in a short while. Up till now a collection of his fiction has come into sight. His fiction provides a developing outlook towards many social, religious and political issues, social issues discuss society in different dimensions like anti-sentimental attitude of society, misguidedness, immoderate behaviors, old customs, condemn the critics criticizing the new generation, damage arising from old thinking, generation gap, altercation in relationships, household rights etc. His fiction also describes how politics and religion can be used as a tool to fulfill an individual’s desire. There we find a pen picture of zero tolerance, cruelty and anti-sentimental attitude in politics caused by capitalism. Saeed Naqvi has enriched Urdu literature with his high work in fiction after discussing issue like unchecked bloodshed of Muslims in the name of religion and many of the same.